2010
DOI: 10.1007/s11273-010-9187-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local and landscape-scale habitat variables on abundance and reproductive success of wetland birds

Abstract: Both local and landscape-scale habitat variables influence the abundance of wetland breeding birds. Few studies, however, simultaneously assess the effects of habitat variables at multiple spatial scales or consider effects on reproductive success. Therefore, we examined the effects of wetland and landscape-scale habitat variables on the abundance of nine breeding bird species and the effects of nest, wetland, or landscape-scale habitat variables on the nest success, clutch size, or number of fledglings of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 67 publications
3
52
0
Order By: Relevance
“…The idea that the optimal landscape extent for assessing biotic integrity might be speciesspecific is supported by other bird studies. For example, Tozer et al (2010) found that both Marsh Wren and Least Bittern abundances were related to the proportion of wetland in the surrounding landscape, but at different spatial extents. They suggest that the positive relationship between wetland habitat and bird abundance is due to a greater influx of dispersing individuals in landscapes with a greater proportion of wetland habitat, although such a mechanism would apply equally to plants through the dispersal of their propagules, either by wind, water, or animal vectors.…”
Section: Spatial Extent Influences Relationship Between Land Cover Anmentioning
confidence: 99%
“…The idea that the optimal landscape extent for assessing biotic integrity might be speciesspecific is supported by other bird studies. For example, Tozer et al (2010) found that both Marsh Wren and Least Bittern abundances were related to the proportion of wetland in the surrounding landscape, but at different spatial extents. They suggest that the positive relationship between wetland habitat and bird abundance is due to a greater influx of dispersing individuals in landscapes with a greater proportion of wetland habitat, although such a mechanism would apply equally to plants through the dispersal of their propagules, either by wind, water, or animal vectors.…”
Section: Spatial Extent Influences Relationship Between Land Cover Anmentioning
confidence: 99%
“…The positive relationship between Typha sp. and counts of breeding marsh birds has been found by other studies and in other regions of North America (Tozer et al 2010, Lupien et al 2014. In particular, the robust leaves of Typha sp.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, larger wetlands may provide a greater variety of food items that can accommodate more individuals and species Dinsmore 1986, Brown and. Additionally, several SMBs such as the Least Bittern, Pied-billed Grebe, and American Coot prefer larger wetlands, but this may be due to greater water depths and emergent vegetation cover (Tozer et al 2010, Baschuk et al 2012, Monfils et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations